2017
DOI: 10.1007/s12020-017-1352-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an education course delivered to community health workers in diabetes control: A randomized clinical trial

Abstract: In this study, a significant decrease in HbA1c was observed during patients' follow-up, but it was similar in intervention and control groups. The diabetes mellitus education course delivered to community health workers was able to improve patients' lipid profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 27 publications
0
20
0
3
Order By: Relevance
“…Of the 63 studies included in the review, there were 32 randomised controlled trials (from 33 publications),24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56 11 cluster randomised trials,57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67 and 20 before-and-after studies68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87 (appendix pp 3–38). 50 studies were done in Asia and Africa.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 63 studies included in the review, there were 32 randomised controlled trials (from 33 publications),24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56 11 cluster randomised trials,57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67 and 20 before-and-after studies68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87 (appendix pp 3–38). 50 studies were done in Asia and Africa.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies41, 49, 51, 56 did not mention randomisation methods and the randomisation method was unclear in five studies 24, 25, 27, 36, 59. Only 15 of 43 trials reported details of allocation concealment 29, 32, 35, 36, 39, 45, 46, 47, 50, 53, 55, 63, 64, 65, 66, 67. Two studies29, 30 reported participant blinding and 14 studies25, 26, 29, 40, 44, 46, 50, 51, 52, 53, 55, 66 reported outcome assessor blinding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were nine trials each from Brazil and China. The studies were done in primary health centres (n=10 [22%]), 31,33,35,50,63,65,66,70,72,74 diabetes clinics or community health centres (n=12 [26%]), 32,34,36,45,47-49,51,67,68,71,75 hospitals (n=21 [44%]), 39,[40][41][42][43][44]46,52,53,[55][56][57][58][59][60][61]62,64,69,73,76 and community settings (n=3 [9%]). 37,38,54 The sample size ranged from 53 participants 65 to 4393 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Non-pharmacological inter ventions included assessment, monitoring, lifestyle education, and counselling for the management of diabetes. The interventions were delivered by pharmacists (n=16 [35%]), 41,42,44,45,[52][53][54][55][56]61,62,66,[68][69][70]73 nurses (n=19 [41%]), 31,[33][34][35][36]39,40,43,46,49,57,59,64,65,67,71,72,75,77 dietitians or nutritionists (n=4 [9%]), 47,50,58,74 community health workers (n=5 [11%]), 32,37,38,48,63 or a combination of community health centre staff, nurses, or pharmacists (n=2 [4%]). 51,60 Of the 46 trials, 37 (80%) delivered a non-pharmacological intervention, eight (17%) had both non-pharmacological and pharmacological components, 38,…”
Section: Resultsmentioning
confidence: 99%